Implementation of Information System in Submitting Employees’ Annual Leave at PT. Tesco Indomaritim - Nurwidayat, Arif; Sudarsono, Bibit; Pratiwi, Kharisma; Havity, Marita Dwi (Politeknik Ganesha Medan, 2019)
The progress of a company is always supported by appropriate management in managing the company and labor resources. By utilizing one of the developments in web-based computer network technology, it can support the development of information systems in companies so that the flow of information can be delivered quickly and accurately. PT. Tesco Indomaritim needs to change and build a new system in the process of submitting leave to be a computerized and web-based system. In the process of submitting leave by filling in the leave form and making reports using Microsoft Word and Microsoft Excel so that obstacles are still found. The large number of files which accumulate results in difficulties in searching, capturing and losing data. So to overcome this, a Submission Leave Information System was created at PT. Tesco Indomaritim which is expected to be able to provide solutions to the shortcomings of the old system. The web-based annual leave submission system that is made simple and easy to use must be applied in order to facilitate all employees, ease the staffing in making reports, ease for superiors for the proposed leave approval process, so that they are more effective and efficient because they are interconnected indirectly.